ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS DENGAN PERTUMBUHAN LABA SEBAGAI VARIABEL MODERASI: Studi Empiris pada Perusahaan Property dan Real Estate yang terdaftar di Bursa Efek Indonesia tahun 2013-2017 - Ayu Juniyanti (Jurnal Statistika Industri dan Komputasi, 2019)
Abstract. This research was conducted to examine the effect of Company Size, DER and Total Asset Turnover on profitability with profit growth as a moderating variable in Real Estate and Property Companies in 2013-2017. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange (IDX). Sampling is done by using purposive sampling method, which is the determination of samples with specific targets or considerations. The companies selected for the sample in this study are based on these criteria as many as 50 companies. Data analysis using multiple regression methods and data analysis techniques used are Moderated Regression Analysis (MRA). These results indicate that the debt to equity ratio (DER), profit growth, and moderation of earnings growth to firm size, and moderation of earnings growth to total asset turnover (TATO) do not affect profitability. Whereas company size, total asset turnover (TATO), and moderation in earnings growth on the debt to equity ratio (DER) affect profitability. Profitability is explained by variables namely company size, DER, TATO on profitability and profit growth as a moderating variable which is 61.2%. While around 38.8% are influenced by other variables not examined in this study.